PARTISIPASI MASYARAKAT MELALUI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Pada Perusahaan Perkebunan Kelapa Sawit PT. TSP Kabupaten Keerom Provinsi Papua) - MELKIAS MONIM ; Prof. Armanu, SE., M.Sc., Ph.D., Dr. Noermijati, SE., MTM.,Dr. Siti Aisjah, SE., MS (Disertasi Manajemen FEB - UB, 2014)
Corporate social responsibility is a program undertaken by the company to improve the social and environmental isue of the existence of the company. However the implementation of corporate social responsibility is not always improve the welfare of the community and improve the environment. The purpose of this research is to uncover and make sense of social responsibility programs that have been implemented in accordance with the local knowledge and to uncover and interpret the form of community participation in community social responsibility programs in the village Kriku, Yetti and Suskun in East Arso District Kerom District, Papua Province. This study used a phenomenological qualitative research design. This research was conducted at the oil palm plantation companies are located in the District Arso Keerom Papua Province. Informants in this study consisted of individuals within the company officials who carry out the CRS